2007
DOI: 10.1021/jp076113n
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Novel Mesoporous Manganese Oxide Nanostructures and Their Application in Oxidative Decomposition of Formaldehyde

Abstract: Monodisperse manganese oxide honeycomb and hollow nanospheres have been prepared facilely at room temperature by varying the molar ratio of KMnO 4 and oleic acid. These new nanomaterials were characterized by XRD, SEM, EDS, TEM, and BET measurements. They had robust nanostructures and were stable even after ultrasonic treatment (40 kHz, 120 W) for 30 min. A plausible mechanism of the formation of manganese oxide nanostructures was proposed. The manganese oxide nanomaterials showed high catalytic activities for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(183 citation statements)
references
References 65 publications
4
179
0
Order By: Relevance
“…Chen et al have also attributed the enhanced catalytic activity for oxygen reduction of porous Pt nanospheres to both large surface area and high density of defects at the shell surface. 79 An interesting result was reported by Chen et al 74 They found that K x MnO 2 hollow nanospheres demonstrate much higher catalytic activity for oxidative decomposition of formaldehyde than honeycomb nanospheres although the surface area of the latter is nearly two times as high as that of the former. The authors believe it is mainly because that the hollow K x MnO 2 nanospheres could adsorb and retain formaldehyde for a longer period of time than the honeycomb K x MnO 2 nanospheres and eventually enhance the oxidation of formaldehyde.…”
Section: Catalytic Propertiesmentioning
confidence: 86%
See 4 more Smart Citations
“…Chen et al have also attributed the enhanced catalytic activity for oxygen reduction of porous Pt nanospheres to both large surface area and high density of defects at the shell surface. 79 An interesting result was reported by Chen et al 74 They found that K x MnO 2 hollow nanospheres demonstrate much higher catalytic activity for oxidative decomposition of formaldehyde than honeycomb nanospheres although the surface area of the latter is nearly two times as high as that of the former. The authors believe it is mainly because that the hollow K x MnO 2 nanospheres could adsorb and retain formaldehyde for a longer period of time than the honeycomb K x MnO 2 nanospheres and eventually enhance the oxidation of formaldehyde.…”
Section: Catalytic Propertiesmentioning
confidence: 86%
“…Other different yet related approaches have also been employed to synthesize hollow nanoparticles such as hydrothermal, 72,73 emulsion, 74,75 and micelle 76 methods.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations